Strategi Manajemen Program Bimbingan dan Konseling dalam Meningkatkan Efektivitas Layanan di Sekolah Menengah Kejuruan - Muharleni; Yarmis Syukur; Neviyarni (Suria Academic Press, 2025)
The management of Guidance and Counseling (GC) programs plays a strategic role in determining the success of counseling services in schools, particularly in Vocational High Schools (SMK), where students are oriented toward the world of work. This study aims to analyze effective management strategies for GC programs in improving service effectiveness at vocational schools. A descriptive qualitative approach was employed, involving guidance counselors, school principals, and students as participants. Data were collected through interviews, observations, and documentation studies, then analyzed using the Miles and Huberman interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that effective management strategies for GC programs encompass four key functions: (1) needs-based program planning, (2) collaborative resource organization, (3) innovative service implementation aligned with vocational student characteristics, and (4) continuous data-driven evaluation. The application of these strategies enhanced the effectiveness of counseling services, as reflected in increased student participation, achievement of service goals, and the establishment of a positive school culture. Supporting factors include strong school leadership, professional competence of counselors, and supportive institutional policies. These results emphasize that GC program management is not merely an administrative function but a strategic component essential for delivering high-quality and relevant counseling services that meet the developmental and vocational needs of students in the digital era.